Pulse oximetry screening for critical congenital heart defects in Ontario, Canada: a cost-effectiveness analysis - Mukerji, Amit (Can J Public Health, 2020)
OBJECTIVE: Previously conducted cost-effectiveness analyses of pulse oximetry screening (POS) for critical congenital heart defects (CCHDs) have shown it to be a cost-effective endeavour, but the geographical setting of Ontario in relation to its vast yet sparsely populated regions presents unique challenges. The objective of this study was to estimate the cost-effectiveness of POS for CCHD in Ontario, Canada. METHODS: A cost-effectiveness analysis, comparing POS to no POS, was conducted from the Ontario healthcare payer perspective using a Markov model. The base case was defined as a well-appearing newborn at 24 h of age. Outcome measures, including quality-adjusted life months (QALMs), lifetime costs, and incremental cost-effectiveness ratios (ICER) [ΔCost/ΔQALMs], were calculated over a lifetime horizon. All outcomes were discounted at 1.5% per year. Cost-effectiveness was assessed using an a priori ICER threshold of CAD$4166.67 per QALM (equivalent to CAD$50,000 per quality-adjusted life year). Deterministic and probabilistic sensitivity analyses were conducted to assess parameter uncertainty. RESULTS: Implementation of POS is expected to lead to timely diagnosis of 51 CCHD cases annually. The incremental cost of performing POS was estimated to be $27.27 per screened individual, with a gain of 0.02455 QALMs. This yielded an ICER of CAD$1110.79 per QALM, well below the pre-determined threshold. The probabilistic sensitivity analysis estimated a 92.3% chance of routine implementation of POS being cost-effective. CONCLUSION: Routine implementation of POS for CCHD in Ontario is expected to be cost-effective. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.17269/s41997-019-00280-7) contains supplementary material, which is available to authorized users.